Optimal Convergecast Scheduling Limits for Clustered Industrial Wireless Sensor Networks - Xiaoling Zhang; Wei Liang; Haibin Yu; Xisheng Feng (International Journal of Distributed Sensor Networks)
Increased mobility coupled with a possible reduction of cabling costs and deployment time makes wireless communication an attractive alternative for the industrial process monitoring and control. The major obstacles toward the utilization of wireless industrial networks are predominantly the timeliness and reliability requirements. In this paper, orienting to clustered industrial wireless sensor networks, we analyze the performance bounds of the convergecast scheduling, which is a typical many-to-one communication in wireless industrial networks. The analysis aims to the cluster-line and cluster-tree topologies. Each kind is future divided into three scenarios according to an application parameter, named data update rate. Firstly, we establish the lower bounds on the number of timeslots to finish the intracluster and the intercluster convergecast transmissions. Secondly, we establish the lower bounds on the number of channels based on the lower bounds on the number of timeslots and maximum available channels in a multichannel scenario. Lastly, we carry out the extensive analysis-taking packet retransmissions into consideration so as to meet the reliability requirement. Experiment results validate the correctness and tightness of our theory analysis.